2018
DOI: 10.1007/s10824-018-9320-x
|View full text |Cite
|
Sign up to set email alerts
|

The geography of music preferences

Abstract: Considerable attention has been paid to America's political and economic divides. These divides revolve around class and location, with more affluent, more educated and denser places leaning more open-minded and liberal and less affluent, less educated and less dense places leaning more conservative. We contend that such divides are also reflected and reinforced by preferences, attitudes and predispositions for culture. More specifically we argue that Americans' preferences for music will reflect dimensions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 21 publications
2
16
0
2
Order By: Relevance
“…The first dimension, Intense, characterized by loud, forceful, and energetic music, was consistent with previous studies [15,44,45]. The second dimension, Unique, comprised uncomplicated, unaggressive, soft music, consistent with the findings of different authors [14,46]. Additionally, it is worth noticing that most of the music styles comprising this dimension are originally from Brazil and connected to dance.…”
Section: Discussionsupporting
confidence: 89%
“…The first dimension, Intense, characterized by loud, forceful, and energetic music, was consistent with previous studies [15,44,45]. The second dimension, Unique, comprised uncomplicated, unaggressive, soft music, consistent with the findings of different authors [14,46]. Additionally, it is worth noticing that most of the music styles comprising this dimension are originally from Brazil and connected to dance.…”
Section: Discussionsupporting
confidence: 89%
“…This notion is consistent with the previously reported correlation between understanding and appreciating an artwork (Silvia, 2005(Silvia, , 2006. Similarly, psychological and sociological investigations have shown that more sophisticated and complex musical genres (e.g., folk, bluegrass, blues, jazz, opera, classic) that require more experienced composers with more musical education are preferred by audiences with higher social or professional positions (Mellander, Florida, Rentfrow, & Potter, 2018;Peterson, 1992), higher education (Mellander et al, 2018), and greater intellectual openness (Rentfrow & Gosling, 2003). An analogous relationship also has been found between age and musical preferences; in particular, older people with more experience have been shown to prefer more complex genres (North & Hargreaves, 1997;Rentfrow & Gosling, 2003).…”
Section: Decoding Mechanismssupporting
confidence: 90%
“…We hypothesize that higher levels of education and more varied personal experiences encourage a more diverse conceptual dictionary. Support for this notion comes from the previously cited investigations that have examined the popularity of different genres of music among individuals with different levels of education and of different ages (Mellander et al, 2018;Peterson, 1992).…”
Section: Decoding Mechanismsmentioning
confidence: 99%
“…Florida et al ( 2012 ) offer a study “geographies of scope,” specifically the co-location of organizations in the entertainment industry. Mellander et al ( 2018 ) have mapped geography of music preferences in this journal, but it is the prior (2012) study of geographies of scope that most pertains.…”
Section: Background and Methodologymentioning
confidence: 99%